2020
DOI: 10.17679/inuefd.742503
|View full text |Cite
|
Sign up to set email alerts
|

Sınıf Öğretmenlerinin E-portfolyo Hakkındaki Görüşleri

Abstract: In the study, it was aimed to examine the views of primary school teachers about electronic portfolio (e-portfolio). The purpose of the research was to seek answers to such questions; "what is the awareness of primary school teachers about eportfolio?", "what are the views of primary school teachers about the functions of eportfolio?" and "what are the views of primary school teachers towards the outcomes of the e-portfolio?" "Case study", one of the qualitative research methods, was used in the research. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…It is also understood that limitations caused by distant education model in preschool education will influence children the most and particularly have an impact on the 'socialisation' aspect. The effect of socialisation and socioemotional development, a significant function of school, on social skills of children in kindergarten and primary school period is supported by studies in the literature (Celik, 2019;Erbay, 2008;Pekdogan, 2011).…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
“…It is also understood that limitations caused by distant education model in preschool education will influence children the most and particularly have an impact on the 'socialisation' aspect. The effect of socialisation and socioemotional development, a significant function of school, on social skills of children in kindergarten and primary school period is supported by studies in the literature (Celik, 2019;Erbay, 2008;Pekdogan, 2011).…”
Section: Discussion and Recommendationsmentioning
confidence: 90%
“…In the research, it was concluded that the use of e-portfolio contributed to the efficient use of time by the social studies teacher candidates. However, there are also studies showing that creating and archiving e-portfolios is time-consuming (Barış & Tosun, 2013;Erten, 2015;Gök, Baş & Ayaz, 2020). As a result of the research, it has been reached that the use of e-portfolio provides the participants with individual benefits for permanent learning, preventing test anxiety, and reducing workload.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…Araştırmada elde edilen bulgular doğrultusunda, e-porfolyo kullanımının sosyal bilgiler öğretmen adaylarının zamanı verimli kullanmalarına katkı sağladığı sonucuna ulaşılmıştır. Ancak e-portfolyo oluşturmanın ve arşivlemenin zaman alıcı olduğuna ilişkin araştırmalar da vardır (Barış ve Tosun, 2013;Erten, 2015;Gök, Baş ve Ayaz, 2020). Barış ve Tosun (2013) tarafından yapılan araştırmada öğrenciler e-portfolyo destekli öğretim sürecinin sonunda olumlu tutuma sahip olsalar da e-portfolyo sürecinin olumsuz bir yönü olarak zaman alıcı olduğunu ifade etmişlerdir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
See 1 more Smart Citation
“…Bu noktada öğrencinin kimseden yardım almadan oluşturduğu ürünlerin seçilmesine özen gösterilmesi gerektiği vurgulanmıştır (Kilmen, 2008, 166;Demirören, Aytuğ Koşan ve Palaoğlu, 2009, 21;Kan, 2007, 136-137). Son dönem eğitim çalışmaları incelendiğinde gelişen teknolojiyle birlikte öğrenci ürün dosyalarının takibinde e-portfolyo kullanımının daha etkin bir şekilde gerçekleştirildiği ve bu sayede özellikle ürünlerin depolanmasıyla ilgili fiziki zorlukların aşıldığı anlaşılmaktadır (Shea ve Priyatam, 2019;Farell , 2020;Gök, Baş ve Ayaz, 2020;Akgün ve Şahin Kölemen, 2020).…”
Section: öğRenci Eserlerinin Takip Edilmesiunclassified